Taradhin Principle in Fiduciary Guarantee Parate Execution after the Decision of the Constitutional Court No. 18/PUU-XVII/2019 - Muhammad Tun Samudra (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
This article was analyzes the principle of Willingness in the Execution of fiduciary guarantees after the decision of the Constitutional Court Number 18/PUU-XVII/2019, in practice Parate execution can be carried out either with or without the consent of the debtor, such conditions often lead to acts of coercion and violence from fiduciary guarantee holders, even giving opportunities to arbitrary acts committed by fiduciary recipients (creditors) and degrading the dignity of the debtor. From the research conducted, it was found that the application of the principle of willingness in the Parate Execution of fiduciary guarantees by the Constitutional Court provides benefits and prevents harm to debtor and creditors, this can be seen from the main idea of the Court which states that parate Executions should no longer be carried out without an agreement of the customer's and the customer's willingness to return the collateral. If the customer does not admit the defaulted, then the fiduciary holder can submit an application through fiat Execution to the Court.